A Study to Estimate the Prevalence of Occupational Exposure to Blood and Body Fluids among the Health Care Workers in a Teaching Hospital Attached to Bangalore Medical College and Research Institute (BMCRI) - Shibi Selladurai; Nimra Shireen (Medsci Publications, 2019)
Background: Health care workers (HCWs) are at a high risk of sharp injuries and contact with blood and body fluids, exposing them to over 20 different blood borne pathogens, the most common being hepatitis B virus (HBV), hepatitis C virus (HCV) and Human immunodeficiency virus (HIV).This study was carried out to esti- mate prevalence of accidental exposure to blood & body fluids dur- ing preceding 12 months among HCWs in a tertiary hospital in Ban- galore. Methods: A semi-structured questionnaire was used to study 240 HCWs during a 3 months period (September-November) in a teach- ing hospital in Bangalore. Results: Occupational exposure to blood & body fluids in the pre- ceding 12 months was reported by 54.5% of the respondents. Needle stick injuries (NSI) was the most common mode of such exposures (87%). Only 40.4% of the affected individuals had reported the inci- dent. Conclusion: Occupational exposure to blood & body fluids was a common occurrence in study sample. There was gross under-re- porting of such incidents leading to a lack of proper post exposure prophylaxis (PEP).